Analysis of Aging Transformation Strategy of Old District in Shenyang - Li, Ze (Transactions on Social Science, Education and Humanities Research, 2024)
With the development of society, the number of elderly population in China is increasing year by year. According to the current level of economic development and aging characteristics in China, the home pension model is the current mainstream pension model in China. As an important carrier to meet the needs of the elderly, the degree of "aging" in old residential areas is directly related to the quality of life of most elderly people. As times change, many old village due to the construction age, long use fixed number of year, old related facilities, difficult to meet the needs of the elderly increasingly rich life, letter to repair, so the implementation of old village suitable aging transformation, is in order to ensure the elderly health and safety, the key to improve the quality of life, has the social value and research significance.